2019
DOI: 10.4187/respcare.07205
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High-Flow Nasal Cannula Oxygen Therapy in Immunocompromised Subjects With Acute Respiratory Failure

Abstract: BACKGROUND: Various studies have been performed to examine the effect of high-flow nasal cannula (HFNC) in immunocompromised patients with acute respiratory failure (ARF). However, the results were inconsistent. Thus, we conducted a meta-analysis to evaluate the effect of HFNC oxygen therapy in immunocompromised patients with ARF versus conventional oxygen therapy and noninvasive ventilation (NIV). METHODS: Relevant studies published prior to May 11, 2019, were systematically searched. The primary outcome was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 53 publications
0
14
0
2
Order By: Relevance
“…Full-text review of 38 potentially eligible studies identified 20 eligible studies. Of these, 17 were systematic reviews (SRs) 15,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] and three were RCTs [41][42][43] (Fig. 1).…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…Full-text review of 38 potentially eligible studies identified 20 eligible studies. Of these, 17 were systematic reviews (SRs) 15,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] and three were RCTs [41][42][43] (Fig. 1).…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…Therefore, a device that produces lesser number of droplets or aerosol is required. The exhaled air dispersion produced by HFNC was limited and the risk of hospital-acquired infection did not increase [19,20]. Therefore, the use of HFNC in NCIP patients is feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a device with less production of droplets or aerosol is required. The exhaled air dispersion produced by HFNC was limited and the risk of hospitalacquired infection did not increase [18,19]. Therefore, the use of HFNC in NCIP patients is feasible.…”
Section: Discussionmentioning
confidence: 99%